"IN THE CITADEL OF SUSA WAS A JEWISH ‘TROUBLE-MAKER’": A SOCIOPOLITICAL READING OF ESTHER 3 AND 4 - Quayesi-Amakye, Joseph (Ghana journal of religion and theology, 2017)
Like most other Bible narratives, the Book of Esther may be read without much attention given to the evaporating humanness of the Jewish actors. The traditional view has been to treat the outcome of the tension between ‘bad’ Haman and ‘good’ Mordecai as divine fiat in favor of the Jews. How much ethical issues are embedded in the story has not been plausibly decoded through the centuries. By means of deconstruction, this paper engages the text critically to uncover the embezzled, hidden ‘other’ in it. Consequently, it brings out several critical ignored spots in the narrative that are necessary for sociopolitical consideration in a world beset with suspicions, religious and ethnic/racial mistrust and hatred.